2021
DOI: 10.1177/17562848211036456
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with moderate-to-severe ulcerative colitis treated with vedolizumab: results from a Polish multicenter, prospective, observational real-life study (the POLONEZ study)

Abstract: Background: Vedolizumab, a humanized antibody targeting the α4β7 integrin, was proven to be effective in the treatment of moderate-to-severe ulcerative colitis (UC) in randomized clinical trials. The aim of the POLONEZ study is to determine the demographic and clinical characteristics of the patients with UC treated with vedolizumab within the scope of the National Drug Program in Poland and to assess the real-world effectiveness and safety of vedolizumab in the study population. Here we report the demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Our study showed that patients naïve to previous biological therapies significantly more often achieved clinical remission at week 14 during vedolizumab induction therapy (70.0% vs. 27.3%; p = 0.023). The same results were observed in POLONEZ study performed by Cichoż-Lach et al This study, conducted prospectively, included adult UC patients eligible for UC treatment with vedolizumab who were recruited from 12 centers in Poland and showed that among biologic-exposed patients (mostly infliximab-treated), 57% had failed to respond to the therapy [ 11 ].…”
Section: Discussionsupporting
confidence: 60%
“…Our study showed that patients naïve to previous biological therapies significantly more often achieved clinical remission at week 14 during vedolizumab induction therapy (70.0% vs. 27.3%; p = 0.023). The same results were observed in POLONEZ study performed by Cichoż-Lach et al This study, conducted prospectively, included adult UC patients eligible for UC treatment with vedolizumab who were recruited from 12 centers in Poland and showed that among biologic-exposed patients (mostly infliximab-treated), 57% had failed to respond to the therapy [ 11 ].…”
Section: Discussionsupporting
confidence: 60%
“…As detailed baseline characteristics of Polish patients showed, at the time of enrollment in the NDP, this population had a more severe disease activity, a higher percentage of biologic-naïve patients, and received the first dose of vedolizumab earlier after UC diagnosis than those described in other European real-world cohorts. 14 The obtained treatment results, which may be impacted by the abovementioned differences, complement the data of clinical trials in relation to a larger patient population and daily clinical practice.…”
Section: Introductionmentioning
confidence: 64%
“…Baseline clinical characteristics of the study group were described previously. 14 BMI, body mass index; IQR, interquartile range. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations